2015
DOI: 10.1007/s00115-014-4179-3
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Versorgungsstrategien in der Gerontopsychiatrie und -psychotherapie

Abstract: Collaborative care models, stepped care interventions in primary care settings and an enhanced inter-professional approach to patient care in old age psychiatry is necessary to improve detection, treatment and ongoing care. Tele-mental health services may become important parts of the provision of mental health services and the effectiveness revealed for in-home tele-health problem solving therapy in old age depression may be an approach to make psychotherapy available to a large number of underserved elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
3
0
2
Order By: Relevance
“…25,26 However, the evidence for innovative mental health care strategies for elderly people is scarce. 27 Most studies using ACT, [28][29][30] HT, [31][32][33][34][35] or CRT [36][37][38] did not specifically report whether the innovative care models reduced AHLS in geriatric populations with mental health care needs. A British study showed that CRT and HT significantly reduced admissions of elderly mentally ill patients, but there was no significant difference in AHLS as compared before and after the introduction of these services.…”
Section: Procedures In Medicine Of the World Health Organization Calledmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 However, the evidence for innovative mental health care strategies for elderly people is scarce. 27 Most studies using ACT, [28][29][30] HT, [31][32][33][34][35] or CRT [36][37][38] did not specifically report whether the innovative care models reduced AHLS in geriatric populations with mental health care needs. A British study showed that CRT and HT significantly reduced admissions of elderly mentally ill patients, but there was no significant difference in AHLS as compared before and after the introduction of these services.…”
Section: Procedures In Medicine Of the World Health Organization Calledmentioning
confidence: 99%
“…Studies of home treatment for older people with physical illness showed that these services help to reduce the number of acute admissions and AHLS . However, the evidence for innovative mental health care strategies for elderly people is scarce . Most studies using ACT, HT, or CRT did not specifically report whether the innovative care models reduced AHLS in geriatric populations with mental health care needs.…”
Section: Introductionmentioning
confidence: 99%
“…B. beim physischen Zugang zur psychotherapeutischen Praxis oder der Fähigkeit, regelmäßige Termine einzuhalten. Komorbidität und Psychotherapie ist ein Thema, das in jüngerer Zeit in der Fachliteratur zunehmend thematisiert wird [7]. Unterstützungsangebote wie z.…”
Section: Besondere Herausforderung: Komorbidität Und Funktionale Einsunclassified
“…Depressive Erkrankungen bei älteren Menschen und ihre Behandlung finden in der Fachliteratur zunehmend Beachtung. Diskutiert werden u. a. eine Unterversorgung und Zugangsbarrieren [1][2][3] sowie die Notwendigkeit spezialisierter Versorgungsformen [4][5][6][7].…”
Section: Introductionunclassified
“…Its patient population has higher prevalence of dementia (Weyerer, 2005; Zank et al , 2009) and higher subdiagnostic criteria for depression (Linden et al , 1998; Wolff and Tesch-Römer, 2017) (Busch et al , 2013). They also have limited access to outpatient services (Holthoff, 2015), which leads to an increase of severely and chronically ill patients in GerP (Hirsch, 2016). Those circumstances indicate that GerP has a higher structural complexity than general psychiatry (GenP), which is traditionally expected to correspond with more difficulties in implementing innovations (Duncan, 1976).…”
Section: Introductionmentioning
confidence: 99%